The Road of Solid Tumor Survival: From Drug-Induced Endoplasmic Reticulum Stress to Drug Resistance - Cao, Shulong; Tang, Jingyi; Huang, Yichun; Li, Gaofeng; Li, Zhuoya; Cai, Wenqi; Yuan, Yuning; Liu, Junlong; Huang, Xuqun; Zhang, Haiyuan (Frontiers in Molecular Biosciences, 2021)
Endoplasmic Reticulum Stress (ERS), which refers to a series of adaptive responses to the disruption of endoplasmic reticulum (ER) homeostasis, occurs when cells are treated by drugs or undergo microenvironmental changes that cause the accumulation of unfolded/misfolded proteins. ERS is one of the key responses during the drug treatment of solid tumors. Drugs induce ERS by reactive oxygen species (ROS) accumulation and Ca2+ overload. The unfolded protein response(UPR) is one of ERS. Studies have indicated that the mechanism of ERS-mediated drug resistance is primarily associated with UPR, which has three main sensors (PERK, IRE1α, and ATF6). ERS-mediated drug resistance in solid tumor cells is both intrinsic and extrinsic. Intrinsic ERS in the solid tumor cells, the signal pathway of UPR-mediated drug resistance, includes apoptosis inhibition signal pathway, protective autophagy signal pathway, ABC transporters signal pathway, Wnt/β-Catenin signal pathway, and non-coding RNA. Among them, apoptosis inhibition is one of the major causes of drug resistance. Drugs activate ERS and its downstream anti-apoptotic proteins, which leads to drug resistance. Protective autophagy promotes the survival of solid tumor cells by devouring the damaged organelles and other materials and providing new energy for the cells. ERS induces protective autophagy by promoting the expression of autophagy-related genes, such as Beclin1 and ATG5-ATG12. ABC transporters pump drugs out the cell, which reduces the drug-induced apoptosis effect and leads to drug resistance. In addition, Wnt/β-catenin signal pathway is also involved in the drug resistance of solid tumor cells. Furthermore, non-coding RNA regulates the ERS-mediated survival and death of solid tumor cells. Extrinsic ERS in the solid tumor cells, such as ERS in immune cells of the tumor microenvironment (TME), also plays a crucial role in drug resistance by triggering immunosuppression. In immune system cells, ERS in dendritic cells (DCs) and myeloid-derived suppressor cells (MDSCs) influences the anti-tumor function of normal T cells, which results in immunosuppression. Meanwhile, ERS in T cells can also cause impaired functioning and apoptosis, leading to immunosuppression. In this review, we highlight the core molecular mechanism of drug-induced ERS involved in drug resistance, thereby providing a new strategy for solid tumor treatment.